2020
DOI: 10.3168/jds.2020-18408
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Chinese consumers' attitudes toward traceable dairy products: A focus group study

Abstract: Dairy products are an essential part of a healthy diet, and dairy is an emerging food industry in China. With rapid economic development, Chinese consumers are increasingly health-conscious and are becoming more selective about the quality and safety of dairy products. Adopting a qualitative approach, we explored Chinese consumers' perception of dairy food safety and attitudes toward traceable dairy products through 9 focus group interviews administered in 4 urban locations in North and South China, with a tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…A reliable authentication and traceability system can constitute an essential instrument for the protection of consumers, reducing the chance of people consuming adulterated or contaminated foods, and increasing supplier control and process safety. Consumers showed limited knowledge about the importance of authentication and traceability of food products [ 3 , 4 ], making essential the dissemination of the potential and reliability of tracing methods with the purpose to increase people’s awareness of the role of food surveillance in health protection and the truthfulness of traceability information.…”
Section: Introductionmentioning
confidence: 99%
“…A reliable authentication and traceability system can constitute an essential instrument for the protection of consumers, reducing the chance of people consuming adulterated or contaminated foods, and increasing supplier control and process safety. Consumers showed limited knowledge about the importance of authentication and traceability of food products [ 3 , 4 ], making essential the dissemination of the potential and reliability of tracing methods with the purpose to increase people’s awareness of the role of food surveillance in health protection and the truthfulness of traceability information.…”
Section: Introductionmentioning
confidence: 99%
“…Previous experience with food safety incidents and habits were critical drivers of food safety. The authors state that defensive behavior and risk perception both increase after negative experiences such as an FBD [9,49,61,98], food safety crisis [100], and specific public incidents (e.g., dairy sector in China [53,77]). Negative experiences could increase the consumption of food perceived as safer (e.g., organic food [97]) and reduce the consumption of food perceived as "risky" such as chicken [91].…”
Section: Hazards and Motivators Of Food Safety Perceptionmentioning
confidence: 99%
“…Many studies have observed the effect of different types of trust, such as trust in the government, media, manufacturers and retailers, and certification. Positive effects of trust have been observed [9,47,50,77,102]. In contrast, many studies have pointed out that consumers have little or no trust in the government, certifications, and institutions [65,71,77,103].…”
Section: Hazards and Motivators Of Food Safety Perceptionmentioning
confidence: 99%
“…With the increase in per capita income and the popularization of healthy consumption concepts, Chinese consumers have a growing demand for dairy products [ 1 ]. The frequent occurrence of dairy product safety incidents has led consumers to pay more attention to the quality and safety of dairy products, and some consumers prefer imported dairy products with high quality and low prices [ 2 ].…”
Section: Introductionmentioning
confidence: 99%